2010
DOI: 10.1001/archneurol.2010.269
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Functional Characterization of Antibodies to Native Aquaporin 4 in Neuromyelitis Optica

Abstract: Background: Antibodies targeting membrane proteins play an important role in various autoimmune diseases of the nervous system. So far, assays allowing proper analysis of such autoantibodies are largely missing. A serum autoantibody to aquaporin 4 (AQP4) is associated with neuromyelitis optica (NMO). Although several assays are able to detect this autoantibody, they do not allow determination of the biological activity of anti-AQP4 antibodies.Objective: To develop a bioassay for quantification and characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 34 publications
0
86
2
1
Order By: Relevance
“…In contrast to CDC, interaction of effector cells with NMO antibody in ADCC does not involve multivalent interaction (38) and so does not require AQP4 clustering in OAPs. It is generally believed that CDC is more important than ADCC in NMO disease pathogenesis (1,39,40); however, direct evidence remains lacking. Involvement of ADCC in NMO would have important implications for NMO therapeutics targeting AQP4 supramolecular assembly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to CDC, interaction of effector cells with NMO antibody in ADCC does not involve multivalent interaction (38) and so does not require AQP4 clustering in OAPs. It is generally believed that CDC is more important than ADCC in NMO disease pathogenesis (1,39,40); however, direct evidence remains lacking. Involvement of ADCC in NMO would have important implications for NMO therapeutics targeting AQP4 supramolecular assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in loop A, or loop C, combined with loop E, reduce NMO-IgG binding, suggesting a key role of OAP-specific interactions at the level of extracellular loops (10). It has been reported that the interaction between NMO-IgG and AQP4-OAPs induces pathogenic mechanisms in NMO by complement-dependent cytotoxicity (CDC), and/or by antibody-dependent cellular cytotoxicity (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…These elegant experiments conclusively proved that the antigen recognized by the NMO-IgG antibody was AQP4. Both the immunohistochemical and the AQP4-transfected HEK cell assays for detecting anti-AQP4 antibody from patient sera were subsequently validated by several groups (Takahashi et al, 2006;Paul et al, 2007;Marignier et al, 2008;Kalluri et al, 2010). These studies definitively prove that the NMO-IgG is an anti-AQP4 antibody.…”
Section: Acute Inflammatory Myelopathies 637mentioning
confidence: 91%